Assessment OF Ki-67 and Bcl-2 Immunohistochemical Markers in Gingival Pyogenic Granuloma: A Comparison with Peripheral Giant Cell Granuloma - Ameera Kamal Khleel (Journal of Global Pharma Technology, 2016)
Background and objectives: Pyogenic granuloma (PG) and peripheral giant cell granuloma (PGCG) are common focal reactive hyperplastic lesions affecting the gingiva.  The aim of the present research was to study the clinical and the immunohistochemical expressions of Ki-67 and Bcl-2 for gingival pyogenic granuloma in comparison with peripheral giant cell granuloma. Materials and Methods: Formalin fixed, paraffin-embedded biopsy specimens of (48) gingival pyogenic granuloma and (39) peripheral giant cell granuloma were used in the study.  Clinical and immunohistochemical analysis for Ki-67 and Bcl-2 were studied in pyogenic granuloma and peripheral giant cell granuloma. Results: The female to male ratio of pyogenic granuloma and peripheral giant cell granuloma was (1.18:1 and 1.43:1) respectively. The mean age was (32.47±19.575 and 35.03±18.22) year respectively. The pyogenic granulomas were mostly affecting the maxillary gingiva, while peripheral giant cell granulomas were mostly affecting the mandibular gingiva. Reactivity percentages for Ki-67 and Bcl-2 markers were significantly higher in peripheral giant cell granuloma compared to pyogenic granuloma (21.71±8.596% vs. 12.68±6.117 %, and 38.77±20.396% vs. 3.547±1.59%) respectively. Conclusion: PGCG showed more proliferative and anti apoptotic activity compared with PG.  This can add insight to the clinical behavior and might reflect the differences in pathogenesis of these lesions.Keywords: Pyogenic granuloma, Peripheral giant cell granuloma, Ki-67, Bcl-2.